Controllable methane hydrate formation through trace carbon dioxide charging. (1st September 2017) - Song, Yuanmei; Wang, Fei; Liu, Guoqiang; Luo, Shengjun; Guo, Rongbo
Graphical abstract: Highlights: Methane hydrate formation was accelerated by increasing CO2 content. The easier formed CO2 nuclei triggered faster hydrate nucleation. Addition of a certain amount of CO2 in induction period triggered fast methane hydrate growth stage. Abstract: An initial method to efficiently control methane hydrate formation process was investigated in this work. This method included an in-situ injection of a small amount of CO2 into the reactor during the nucleation stage to explore hydrate formation in 0.5 mmol/L sodium dodecyl sulfate (SDS) solutions. Results showed that charging CO2 higher than 2% in the mixed gases could induce immediate methane hydrate growth stage. Furthermore, when 3% CO2 was injected into the reaction system at different time points, the times required for hydrate formation were all shortened significantly. Especially at the injection points of more than 30 min, the subsequent crystals growth began immediately after CO2 injection. Besides, the formed hydrates tended to aggregate in the vicinity of CO2 injection zones. Such promotion effect was possibly caused by the triggering effect of preferentially formed CO2 hydrates in the reaction system. This work provides a novel and simple method to control hydrate formation process, which is of great significance to the transportation and storage of natural gas.